Giant cell tumor of tendon sheath of the foot: A rare case report - Khan, Shujaat; Raghava, Vinod; Tikoo, Dipiya; Parveen, Shahnaz; Chaturvedi, Shweta; Joshi, Shashwat; kaur, Gagandeep (Indian Journal of Case Reports, 2026)
Giant cell tumor of tendon sheath (GCTTS) is a benign soft-tissue lesion arising from the synovium of tendon sheaths and is most commonly encountered in the fingers and hand. Involvement of the foot is uncommon and may lead to delayed diagnosis due to its indolent clinical course. We report a case of a 36-year-old male who presented with a painless, gradually progressive swelling over the right foot for 5 years. Radiological evaluation, including ultrasonography and magnetic resonance imaging, suggested a soft-tissue tumor with features suspicious of GCTTS. Fine-needle aspiration cytology revealed a giant cell-rich lesion. Complete surgical excision was performed, and histopathological examination confirmed the diagnosis of localized type GCTTS. This case emphasizes the importance of clinicoradiological correlation and histopathology in the diagnosis of long-standing soft-tissue swellings of the foot.